2018
DOI: 10.5414/cn109197
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E supplementation improves high-densitiy lipoprotein and endothelial functions in end-stage kidney disease patients undergoing hemodialysis

Abstract: In ESKD patients undergoing hemodialysis, vitamin E supplementation significantly improved the HDL function of CEC and, in diabetic patients, endothelial function. These effects were independent of Hp phenotype.
.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…As previously reported, supplementation of -tocopherol increased CEC in patients with end-stage renal disease 11) , a finding consistent with that in patients with type 1 diabetes 12) . CEC changes correlated positively with serum -tocopherol and -tocopherol in this study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As previously reported, supplementation of -tocopherol increased CEC in patients with end-stage renal disease 11) , a finding consistent with that in patients with type 1 diabetes 12) . CEC changes correlated positively with serum -tocopherol and -tocopherol in this study.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, improving CEC of HDL particles, rather than increasing HDL-C levels, is considered to be a novel target for the prevention of CVD. Although HDL has been shown to have antioxidant properties 7,8) and certain antioxidant foods reportedly increase CEC 9,10) , there have been few studies focusing on the relationships of CEC with oxygen radical absorbance capacity (ORAC) and lipophilic dietary antioxidant levels in serum 11,12) .…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown in in vitro, in vivo and clinical studies that antioxidants activate the NO/eNOS pathway through decreasing in the amount of ROS [ 56 , 57 , 58 ]. Several lines of evidence have shown that antioxidants including vitamin E [ 59 , 60 , 61 , 62 ], vitamin B12 [ 63 ], alpha-lipoic acid [ 62 ], N-acethlcystein [ 64 , 65 ], flaxseed [ 66 ], L-carnitine [ 67 ], catechins [ 68 ], coenzyme Q10 [ 69 ], pycnogenol [ 70 ], and chlorogenic acids [ 71 ] improve or augment endothelial function in patients with CVD and in subjects who have cardiovascular risk factors as well as healthy subjects. However, not all of the studies showed the beneficial effects of antioxidants on endothelial function [ 72 , 73 , 74 , 75 , 76 ].…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Antioxidant supplementation in subjects with nephropathy has shown promising results in slowing progression of atherosclerosis: Even a short-term, low dose, vitamin E supplementation (almost 300 mg/die) seems to improve, in patients with ESRD undergoing hemodialysis, the flow-mediated arterial dilation (FMD), an indirect method to assess the endothelial function [22]. These vascular effects could mediate the protective role of tocopherols and tocotrienols on DKD.…”
Section: Diabetic Nephropathy and Vitamin Ementioning
confidence: 99%